2-[(4-Phenylthiazol-2-yl)hydrazonomethyl]phenol - Dincer, M; Özdemir, N; Cukurovali, A; Yilmaz, I (Int Union Crystallography, 2005)
In the title compound, C16H13N3OS, the plane of the -C-CH =N-NH-C- bridge makes dihedral angles of 7.9 ( 2) and 11.9 ( 4)degrees with the planes of the phenol and thiazole rings, respectively. In the molecule, there are two intramolecular interactions of type O-H center dot center dot center dot N and C-H center dot center dot center dot N. In the crystal structure, there are two intermolecular interactions of type C-H center dot center dot center dot N and N-H center dot center dot center dot O, leading to the formation of dimers.
Keywords: 2-Aminothiazole; Crystal